Relevansi Hadis-Hadis Pendidikan terhadap Penguatan Karakter Peserta Didik di Era Digital - Suhardi; Fatimah Purba; Leli Hasanah Lubis; Irhamuddin; Rokiba Hasibuan (Insan Zenius Ilmiah, 2026)
The development of the digital era brings significant changes to the world of education, especially in the formation of students' character. The ease of access to information and the massive use of digital technology not only have a positive impact but also pose various ethical and moral challenges. Therefore, character education has become an urgent necessity to shield students from the negative influences of technological development. Educational hadiths, as one of the main sources of Islamic teachings, play a strategic role in shaping the character of students with noble morals. This research aims to analyze the relevance of educational hadiths to the strengthening of character education for students in the digital era, particularly in building responsible digital ethics. The research method used is qualitative research with a library research approach thru the analysis of hadith books and Islamic education literature. The research results show that the values contained in educational hadiths, such as honesty, responsibility, discipline, manners, and self-control, have a strong relevance in shaping the character of students amidst the dynamics of the digital era. In addition, these values also play a role in shaping moral awareness and critical thinking skills in filtering digital information. The integration of hadith values in Islamic education can strengthen students' character to be wise in utilizing technology and ethical in the digital space.